A comparative study of the structural adjustment strategies in Taiwan and Korea. - Chng, Lai Hoon (2014)
In any international comparison of economic performance during the past three decades, four East Asian economies – Hong Kong, Singapore, Taiwan and South Korea – performed most brilliantly in terms of both of their absolute achievement and the rate of progress. Although these economies still lag behind the developed countries in real income and per capita income, in terms of other indicators they rank far ahead of all economies. So what important factors had fuelled their economic performance? The objective of this project is to identify the factors which were important in their successes. An analysis of each country/region individually does not give a complete picture. The experiences of city-states/regions such as Hong Kong and Singapore, which are substantially dependent on unique geographies and histories, are irrelevant for most of the developing countries. In contrast, Taiwan and Korea having initial conditions similar to most other developing countries/regions are more relevant for these countries/regions. Therefore, a comparative study is conducted for Taiwan and Korea to see what factors they have in common. The ultimate purpose is to ascertain whether any general principles can be induced from the successful experiences of these two economies. Which factors are more important than the rest? To what extents have their specific economic policies been favourable to growth? Are certain institutional environments more conducive to economic growth? From these questions, we would like to draw any lessons that other LDC can be learnt from them.